A semi-empirical model for mean wind velocity profile of landfalling hurricane boundary layers. Issue 180 (September 2018) - Snaiki, Reda; Wu, Teng
Abstract: The existence of the super-gradient-wind region, where the tangential winds are larger than the gradient wind, has been widely observed inside the hurricane boundary layer. Hence, the extensively used log-law or power-law wind profiles under near-neutral conditions may be inappropriate to characterize the boundary layer winds associated with hurricanes. Recent development in the wind measurement techniques overland together with the abundance of data over ocean enabled a further investigation on the boundary layer wind structure of hurricanes before/after landfall. In this study, a semi-empirical model for mean wind velocity profile of landfalling hurricanes has been developed based on the data from the Weather Surveillance Radar-1988 Doppler (WSR-88D) network operated by the National Weather Service and the Global Positioning System (GPS) dropsondes collected by the National Hurricane Center and Hurricane Research Division. The proposed mathematical representation of engineering wind profile consists of a logarithmic function of the height z normalized by surface roughness z 0 ( z / z 0 ) and an empirical function of z normalized by the height of maximum wind δ ( z / δ ). In addition, the consideration of wind direction in terms of the inflow angle is integrated in the boundary layer wind profile. Field-measurement wind data for both overland and over-ocean conditions have been employed to demonstrate the accuracy of simulation and convenience in use of the developed semi-empirical model for mean wind velocity profile of landfalling hurricanes. Highlights: A semi-empirical model for mean wind velocity profile of landfalling hurricanes has been developed. The model consists of a logarithmic function of height z and an empirical function of z normalized by height of maximum wind. The proposed height of maximum wind highlights the contribution from both the inertial stability and surface roughness. Consideration of wind direction in terms of inflow angle is integrated in the boundary layer wind profile. Wind data for both overland and over-ocean conditions have been employed to develop the semi-empirical wind profile model.